The Effectiveness of Implementing Population Service System through Klampid New Generation - Abdurrohim Abdurrohim; Tukiman Tukiman (Univiversitas Dr. Djar Wattiheluw, 2024)
The study investigates the effectiveness of the Klampid New Generation program in providing services to the Kapas Madya Baru village in Surabaya city. Implemented as part of the Minimum Service Standards (MSS) program, Klampid New Generation aims to improve public services and governance. The research, conducted using a descriptive qualitative approach, involves observation, interviews, and documentation. While the program effectively extends services to the village, there are areas for improvement, such as incomplete optimization of resources, funds, facilities, and infrastructure. However, the program demonstrates effectiveness in both quantity and quality of services provided, as well as in meeting production deadlines and procedural requirements.